Impact of trade openness on bank risk-taking behavior: Evidence from a developing country - Sk Alamgir Hossain; Syed Moudud-Ul-Huq; Marufa Binta Kader (Cogent Economics & Finance, 2020)
This study investigates the impact of trade openness along with bank size, bank growth, liquidity, deposit insurance, industry centralization, and capital stringency on risk-taking behavior of commercial banks of Bangladesh. To examine the relationships, it considers 32 commercial banks over a period of 2000 to 2017. The main result of this study reveals that trade openness provides ample opportunities in lending activities of commercial banks and aids decreasing credit risk as well as overall bank risk. Hence, it has great implications for the policymakers to promote trade openness and make banks more competitive.
Keywords: 330; credit risk; trade openness; liquidity; size; capital stringency